Conceptions held by health professionals on violence against children and adolescents within the family (Revista Latino-Americana de Enfermagem, 2008)
The present study sought to understand the conceptions held by health professionals with regards to violence within the family against children and adolescents. Qualitative case-study methodology and techniques of participant observation, interviewing, and search in documents were used. Participants were staffed in a government-run Family Health Basic Unit in Brazil. Health professionals were found to associate violence with the economic, social, and political juncture and with cultural aspects; for some, violent acts are part of the intergenerational cycle and family dynamics. Physical punishment, considered as violence by some, is advocated as an educational measure by others. Participants also base their definition of violence on an a priori construction of subjects as either victims or aggressors, thus missing the relational dimension of the phenomenon. Health professionals were found to have difficulty in understanding violence in the context that gives it a meaning and to recognize it as consequence of a complex relational dynamics.